2016
DOI: 10.1080/19336950.2015.1134068
|View full text |Cite
|
Sign up to set email alerts
|

Governing effect of regulatory proteins for Cl/HCO3 exchanger 2 activity

Abstract: Anion exchanger 2 (AE2) has a critical role in epithelial cells and is involved in the ionic homeostasis such as Cl ¡ uptake and HCO 3 ¡ secretion. However, little is known about the regulatory mechanism of AE2. The main goal of the present study was to investigate potential regulators, such as spinophilin (SPL), inositol-1,4,5-trisphosphate [IP 3 ] receptors binding protein released with IP 3 (IRBIT), STE20/SPS1-related proline/alanine-rich kinase (SPAK) kinase, and carbonic anhydrase XII (CA XII). We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The weak cationic cluster is consistent with the idea that AE2 neither exhibits autoinhibition, nor is rescued by IRBIT. Indeed, IRBIT does not stimulate AE2 (Jeong & Hong, ). SLC4A3 (Fig. B ).…”
Section: Discussionmentioning
confidence: 99%
“…The weak cationic cluster is consistent with the idea that AE2 neither exhibits autoinhibition, nor is rescued by IRBIT. Indeed, IRBIT does not stimulate AE2 (Jeong & Hong, ). SLC4A3 (Fig. B ).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Cl − was evaluated from N -(Ethoxycarbonylmethyl)-6-methoxyquinolinium bromide (MQAE, Thermo, E-3101) fluorescence as previously described ( Park et al, 2013 ; Jeong and Hong, 2016 ). HEK293T and primary isolated SMG cells seeded on coverslips were treated with 5 mM MQAE for 30 min at room temperature and perfused with NaCl-based solution until signal stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we found that AE2 localized in the plasma membrane of submandibular ducts. Recently, our previous study revealed the regulatory role of SPL on the AE2, wherein SPL enhances the chloride bicarbonate exchanger (CBE) activity in vitro ( Jeong and Hong, 2016 ). However, the role of SPL in the regulation of basolateral AE2 and Cl − /HCO 3 − balance in exocrine glands remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The SPAK phosphorylation site of NBCe1-B is S65 and T49 in the first 85 N-terminus residues, which acts as an autoinhibitory domain (AID) of NBCe1-B [39]. More recently, Lee et al and Jeong et al suggested that scaffolding protein SPL, as an actin cytoskeletal modulator, binds to AE2 and induces the enhanced AE2 activity [41,42]. SPL consists of a binding motif for F-actin, receptor, and canonical PP1 (R-K-I-H-F motif); PDZ domain; and three coiled-coil (C-C) domains [55].…”
Section: Regulatory Moleculesmentioning
confidence: 99%
“…SPL consists of a binding motif for F-actin, receptor, and canonical PP1 (R-K-I-H-F motif); PDZ domain; and three coiled-coil (C-C) domains [55]. Actually, the SPL can enhance AE2 activity through the 1-480 amino acid residues containing F-actin binding motif, receptor binding motif, and PP1 binding motif [42]. In addition, SPL activity is regulated by Ca 2+ signaling with kinases including SPAK and Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) [41].…”
Section: Regulatory Moleculesmentioning
confidence: 99%